Directions in self consolidating concrete research : a bibliometric study - Mymoon, M.; Mahendran, S.; Poorna, R. Lakshmi; Suryakala, S. (Journal of Structural Engineering, 2024)
In this paper the bibliometric analysis of the growth and development of research in the field of Self Consolidating Concrete or Self Compacting Concrete (SCC), based on the scientific literature available from Web of Science during the period from 1997 to 2013. Self-consolidating concrete (SCC) or self-compacting concrete, as it’s sometimes known, arrived as a revolution in the field of concrete technology. During the study period a total of 1579 papers were published in this research area. Data has been extracted using specialized bibliometric software such as Histciteᵀᴹ and Bibexcel. An in-depth analysis has been done to understand the growth metrics of this research area.